Human physiology, biochemistry, and basic medicine - Cole, Laurence A.; Kramer, Peter R.
Human Physiology, Biochemistry and Basic Medicine is a unique perspective that draws together human biology, physiology, biochemistry, nutrition, and cell biology in one comprehensive volume. In this way, it is uniquely qualified to address the needs of the emerging field of humanology, a holistic approach to understanding the biology of humans and how they are distinguished from other animals. Coverage starts with human anatomy and physiology and the details of the workings of all parts of the male and female body. Next, coverage of human biochemistry and how sugars, fats, and amino acids are made and digested is discussed, as is human basic medicine, covering the science of diseases and human evolution and pseudo-evolution. The book concludes with coverage of basic human nutrition, diseases, and treatments, and contains broad coverage that will give the reader an understanding of the entire human picture. -- Provided by publisher